2014
DOI: 10.3390/ijms150813720
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant Mediated Biosynthesis of Selected Metallic Nanoparticles

Abstract: Developing a reliable experimental protocol for the synthesis of nanomaterials is one of the challenging topics in current nanotechnology particularly in the context of the recent drive to promote green technologies in their synthesis. The increasing need to develop clean, nontoxic and environmentally safe production processes for nanoparticles to reduce environmental impact, minimize waste and increase energy efficiency has become essential in this field. Consequently, recent studies on the use of microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…There is considerable interest in biosurfactant mediated nanoparticles synthesis as it is thought to be environmentally benign process (Plaza et al, 2014). Mukherjee et al (2002) and Ahmad et al (2003) have reported the biological synthesis of gold and silver nanoparticles using microorganisms intracellularly and extracellularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable interest in biosurfactant mediated nanoparticles synthesis as it is thought to be environmentally benign process (Plaza et al, 2014). Mukherjee et al (2002) and Ahmad et al (2003) have reported the biological synthesis of gold and silver nanoparticles using microorganisms intracellularly and extracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles are usually synthesized by physicochemical methods that involve the use of high pressure, temperature and energy; as suggested by Plaza et al (2014) the synthesis of nanoparticles using chemical methods are usually associated with the formation of toxic by-products. Therefore, the use of biosurfactants/biological materials for synthesis and stabilization of nanoparticles is gaining importance since the last decade (Kasture et al, 2008; Kumar C. G. et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that extraction from whole cell-containing culture in batch-fermentation at 72 h gave the highest biosurfactant yield of 34.06 g/l. The increase in the yield may be due to the combined amounts of biosurfactant extracellularly, intracellularly as well as on the cell surface, leading to a high level of biosurfactant detected [24].…”
Section: Comparison Of Biosurfactant Extraction From the Two Methods mentioning
confidence: 99%
“…According to Plaza et al [47] Lipopeptide biosurfactants can also be used in the synthesis of nanoparticles. According to Reddy et al [48] Surfactin can be used as both the template and stabilizing agent in the synthesis of silver and gold nanoparticles.…”
Section: Lipopeptides In Nanotechnologymentioning
confidence: 99%